Comparison of the ability of alternative birthweight and fetal weight standards to identify preterm newborns at increased risk of perinatal death. Issue 12 (31st May 2013) - Ferdynus, C; Quantin, C; Abrahamowicz, M; Burguet, A; Sagot, P; Gouyon, J‐B
<x xml:space="preserve">Abstract</x> Objective To compare prediction of perinatal deaths among preterm infants based on fetal weight standards versus a new subpopulation‐based birthweight standard. Design Population‐based cohort study. Setting France. Population A total of 9100 preterm singletons, born between 24 and 36 weeks of gestation in 2000–09, in Burgundy (France). Methods We first classified all newborns as either small for gestational age (SGA) or not, based on alternative fetal weight or birthweight standards, including a new birthweight standard that excludes infants born to mothers with disease related to the weight of a fetus. Based on discrepancies between the different classifications, we then divided the newborns into four groups, and compared their risks of stillbirth and in‐hospital death, using a generalised linear model with relative risks (RR). Main outcome measures Perinatal deaths, including, in separate analyses, stillbirths and in‐hospital deaths. Results The preterm infants classified as SGA by our new subpopulation‐based birthweight standard but not by the conventional birthweight standard had a significantly higher risk of both stillbirth (RR = 2.6; 95% confidence interval [95% CI] = 1.9–3.6) and in‐hospital death (RR = 2.8; 95% CI = 1.8–4.5). In contrast, no risk increase was found for infants classified as SGA by the fetal standard only (RR = 1.1; 95% CI = 0.7–1.7 for stillbirths, and RR = 0.5; 95% CI = 0.3–1.3 for in‐hospital deaths). Conclusions Our subpopulation‐based birthweight standard identified a subgroup of preterm newborns who have significantly increased risks of perinatal death but are not classified as SGA by the conventional birthweight standard. In contrast, the subgroup classified as SGA by the fetal standards only, but not by our subpopulation‐based birthweight standard, had no increased risk of mortality, compared with non‐SGA infants.